Planning for the future: the case of XYZ Farms - Lichty, Kayla (Kansas State University, 2017)
XYZ Farms, a family farming operation located in Northeast Iowa, has been in business since 1924. Currently the operation utilizes 1,300 acres of farm ground to produce corn, soybeans and alfalfa and feeds 3,000 head of hogs and 500 head of cattle annually. The family operation has evolved over the years and has passed ownership down within the family from generation to generation. It has come time that the operation’s current owners are looking to retire and peacefully transition the family operation on to the next generation. A non-conventional case study structure will highlight and assess the history of the family operation and introduce them to current practices and ownership. The purpose of this study is to evaluate and create a feasible transition plan for XYZ Farms, while minimizing the social and economic costs associated with farm business succession. Further analysis will allow the operation to identify and utilize a succession planning framework, which is important for farm families to possess when looking to build and begin the planning process. Quantitative, along with qualitative, analysis are utilized to understand the operations need for succession planning and the feasibility of doing so. Findings indicate that it is advantageous to work through a sound succession plan including an open line of communication with both current and future owners of the operation. The ability to have upfront conversations and meetings will allow for the discussion of the operation’s future between both parties involved. By implementing a sound and feasible succession plan, XYZ Farms will be able to continue to be a family owned and operated farm for many years to come.
Keywords: Succession planning; SWOT analysis; Family farm; Business plan